Letter (copy) : Basque Children - Tewson, Vincent
1938-03-24 038-0142-001 T.U.C. Secretary's. HVT/FC/345. 24th March, 1938. Mr. D. Lewry, 10, Waverley Avenue, Sutton, SURREY. Dear Sir, BASQUE CHILDREN. I have your letter of the 19th instant asking for the assistance of the General Council in supplying paint for the decoration of your home for Basque children. I need hardly say that we are very interested in the work which your Committee is doing in caring for the Basque children, but so far as we are concerned all the financial assistance which we are able to give is sent direct to the National Committee. Nevertheless, I hope your appeal will be successful in other directions. I know the National Committee are in desperate straits for money, but perhaps you might have a word on the telephone with Miss Arne to see if it is possible for you to have some little assistance, even if it were only £1 or £2. Yours sincerely, Assistant Secretary. off-cuts 292/946/38/142(I)